A Critical Review of Homo Economicus from Five Approaches. (23rd January 2019) - Urbina, Dante A.; Ruiz‐Villaverde, Alberto
Abstract: Neoclassical economics is based on and structured around the notion of homo economicus . The theory of consumer choice, the theory of the firm, industrial organization, and welfare theorems all require the assumption that agents act in accordance with the scheme of individualistic rational optimization. In this context, our contribution is threefold. First, we delimit the notion of homo economicus according to five characteristics or dimensions. Second, we critically review this anthropological scheme from five distinct approaches, namely, behavioral economics, institutional economics, political economy, economic anthropology, and ecological economics. Third, we conclude that the scheme of homo economicus is clearly inadequate and deficient. However, despite its inadequacies, it remains one of the fundamental pillars of the neoclassical paradigm in economics, which allows us to discuss why we have not yet overcome this paradigm.